Urolithin A protects dopaminergic neurons in experimental models of Parkinson's disease by promoting mitochondrial biogenesis through the SIRT1/PGC-1α signaling pathway. Issue 1 (14th December 2021) - Liu, Jia; Jiang, Jingjing; Qiu, Jingru; Wang, Liyan; Zhuo, Jing; Wang, Baozhu; Sun, Deqing; Yu, Shuyan; Lou, Haiyan
Abstract : Schematic illustration of the putative mechanism for Urolithin A effects on mitochondrial biogenesis. Abstract : Mitochondrial dysfunction contributes to the pathogenesis of neurodegenerative diseases such as Parkinson's disease (PD). Therapeutic strategies targeting mitochondrial dysfunction hold considerable promise for the treatment of PD. Recent reports have highlighted the protective role of urolithin A (UA), a gut metabolite produced from ellagic acid-containing foods such as pomegranates, berries and walnuts, in several neurological disorders including Alzheimer's disease and ischemic stroke. However, the potential role of UA in PD has not been characterized. In this study, we investigated the underlying mechanisms for role of UA in 6-OHDA-induced neurotoxicity in cell cultures and mice model of PD. Our results revealed that UA protected against 6-OHDA cytotoxicity and apoptosis in PC12 cells. Meanwhile, administration of UA to 6-OHDA lesioned mice ameliorated both motor deficits and nigral-striatal dopaminergic neurotoxicity. More important, UA treatment significantly attenuated 6-OHDA-induced mitochondrial dysfunction in PC12 cells accompanied by enhanced mitochondrial biogenesis. Mechanistically, we demonstrated that UA exerts neuroprotective effects by promoting mitochondrial biogenesis via SIRT1-PGC-1α signaling pathway. Taken together, these data provide new insights into the novel role of UA in regulating mitochondrial dysfunction and suggest that UA may have potential therapeutic applications for PD.